Mental health and substance use among elite para-athletes: An cross-sectional survey - Tiffany Hartmann; Nikolai Kiselev; Malte Claussen; Christian Imboden; Olivia Stoffel; Andreas Heiniger; Ceren Acarturk; Christoph Kreinbucher-Bekerle; Michael Schaub (Current Issues in Sport Science, 2024)
Objective